2003
DOI: 10.1213/01.ane.0000078586.82810.3b
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Postoperative Pain Management on Immune Response to Surgery

Abstract: Surgery is associated with immune alterations, which are the combined result of tissue damage, anesthesia, postoperative pain, and psychological stress. In the present study, we compared the effects of several postoperative pain management techniques on postoperative immune function. Patients hospitalized for abdominal surgery were randomly assigned to one of three postoperative pain management techniques: opiates on demand (intermittent opiate regimen [IOR]), patient-controlled analgesia (PCA), and patient-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(142 citation statements)
references
References 27 publications
7
125
0
8
Order By: Relevance
“…Papadima and colleagues [26] have found that epidural anesthesia did not suppress postoperative lymphocyte apoptosis in patients receiving major abdominal surgery. Beilin and colleagues [27] showed that epidural analgesia may protect against late (Ͻ72 hours) postoperative lymphocyte suppression, but this effect was not found when restricting the analysis to the early postoperative period. Furthermore, Yokoyama and colleagues [6] found that epidural anesthesia is associated with a transient reduction in natural-killer activity that has been considered unrelated to the pain Avoidance of OLV could also have contributed to the more physiologic lymphocyte response observed in awake patients.…”
Section: Baseline Data and Surgical Resultsmentioning
confidence: 99%
“…Papadima and colleagues [26] have found that epidural anesthesia did not suppress postoperative lymphocyte apoptosis in patients receiving major abdominal surgery. Beilin and colleagues [27] showed that epidural analgesia may protect against late (Ͻ72 hours) postoperative lymphocyte suppression, but this effect was not found when restricting the analysis to the early postoperative period. Furthermore, Yokoyama and colleagues [6] found that epidural anesthesia is associated with a transient reduction in natural-killer activity that has been considered unrelated to the pain Avoidance of OLV could also have contributed to the more physiologic lymphocyte response observed in awake patients.…”
Section: Baseline Data and Surgical Resultsmentioning
confidence: 99%
“…There are however reports contradictory to this, suggesting at least some parts of the immune response may be unchanged [4,5] or enhanced [6]. The various cellular components, namely neutrophils, monocytes, and lymphocytes, have been studied [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The phagocytic activity of neutrophils has been found to be reduced [3] or unchanged [4], while the serum opsonic activity is found to be decreased after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from surgical access trauma per se, other factors favoring VATS lung resection, such as reduced postoperative pain, may also have an important contribution in preserving postoperative cellular immunity by reducing lymphocyte suppression and attenuate proinflammatory cytokine responses [50]. Furthermore, VATS major lung resection encompasses a spectrum of techniques and is not a unified approach [11]; therefore, variations in the use of and size of utility thoracotomy, the number of incisions and port sites used [1], the practice of rib spreading and segmental rib resection [51], as well as the duration of surgery may all have addition effects on postoperative inflammatory and immune responses.…”
Section: Cellular Immunitymentioning
confidence: 99%